The issues of managing the epidemic situation in the health care system in Hungary - Homicskó Árpád Olivér I. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2022)
In my study, I intend to explore the impact of the current epidemic situation on the health care system in Hungary. To this end, the legal environment applicable to the epidemic situation and the measures related to the health care system in the context of the epidemic situation will be presented. I think that in the 21st century and beyond, it will be increasingly important to deal with emerging epidemics, to which all countries must be able to respond appropriately. Managing the epidemic situations effectively and appropriately is in the interest of society as a whole. Furthermore, public health considerations are essential, and every country has to enhance efforts to fight epidemics. In the 21st century, states still have to consider their task to provide the necessary financial resources to combat epidemics. Health care systems should be suitable to meet public health and epidemiological considerations and the demands of general patient care.